Industrial relevant electrical passivation of thin film solar cells interfaces - Cunha, José Miguel Vaz da (2022)
In this thesis, it was developed and studied new rear contact architectures and materials to further increase the optoelectronic performance of ultrathin Cu(In,Ga)Se₂ (CIGS) solar cells. Al₂O₃ and SiO₂ insulator materials were used and studied as passivation layers in the CIGS solar cell’s rear contact. The integrated passivation layers needed to have nano-contact openings to ensure electrical contact between the rear metal and the CIGS layer. Thus, several nano-contact patterns were tested, allowing for an optimization of the solar cell’s rear contact architecture. The passivation layers used on the CIGS solar cell’s rear contact mitigated recombination mechanisms, and, thus, increased the solar cell’s final performance. Another critical aspect of the CIGS solar cell’s rear contact is the low optical reflectivity of the molybdenum (Mo) metal layer. Thus, different metals more reflective than Mo were tested to be used in the rear contact, as well as new rear contact’s architectures to couple both the passivation layers and the metal reflective layers. In this way, it was possible to optimize both rear contact’s passivation and optical reflectivity properties, which allowed to increase the optoelectronic performance of the ultrathin CIGS solar cells. Several electrical measurements, namely current density vs. voltage (J-V) and alternating current (AC) admittance measurements were performed in ultrathin CIGS solar cells, as well as in such solar cells employing passivation layers and/or metal reflective layers. Considering that such solar cells are different from the conventional ones (silicon), additional care was needed to analyse the electrical data. Thus, several nonideal features that can appear in the J-V measurements were analysed and discussed. Moreover, a procedure was shown to accurately estimate the J-V diode parameters, since the process is not straightforward in non-conventional solar cells, such as ultrathin CIGS solar cells. AC electrical measurements, including circuit fitting, are of pivotal importance to couple with J-V electrical analysis, since together they offer a deeper understanding of the optoelectronic effects of the device under study. The AC electrical measurements importance was demonstrated by studying perovskite-based Metal-Oxide- Semiconductor devices to show the relevance of said measurements on technologies other than CIGS.